Corporate restructuring for firm performance improvement: The strategic role of digital transformation and digital human capital - Widiyastuti, Inasari; Rahayu, Agus; Wibowo, Lili Adi; Dirgantari, Puspo Dewi (Diponegoro International Journal of Business, 2025)
Corporate restructuring strategies are critical for improving firm performance, yet the effectiveness of such efforts can vary. In today’s dynamic business environment, integrating digital transformation and digital human capital into these strategies has become increasingly important. This study aims to examine the moderating effect of digital transformation and digital human capital on the relationship between restructuring strategies and firm performance. Using cross-sectional data from 78 publicly listed companies that implemented restructuring strategies in 2023, including IPOs, warrants, and delisting actions, this study assesses their impact on firm’s performance. Results show both organizational and portfolio restructuring positively influence firm’s performance, with digital transformation serving as a critical moderator that enhance portfolio restructuring effectiveness. Financial restructuring, however, demonstrate a negative effect on firm’s performance, moderated only slightly by digital human capital, which does not independently improve performance. The findings highlight the need for alignment between digital initiatives and restructuring strategies to optimize firm outcomes.